PENGARUH LEADER MEMBER EXCHANGE DAN PEMBERDAYAAN TERHADAP KINERJA DENGAN MEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR - Sukadar, 1342020035 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to analyze the Influence of Leader Member Exchange And Empowerment Against Mediated Performance Organizational Citizenship Behavior. In this study, the population of all employees in the health center employees of the District Health Office Tulis, Kandeman, Inpatient Bandar I and Subah. Medium samples were collected based kuseioner many as 131 people who entered as a respondent to the census method. Measurements using a Likert scale of 7 (seven) alternative answers. Test instruments used are validity and reliability. While the test model used is the coefficient of determination and F test (goodnes of Fit). Test this hypothesis using regression analysis. Based on the results of the study can be summarized as follows: (i) Leader Member Exchange is not positive and significant impact on Organizational Citizenship Behavior, (ii) Empowerment positive and significant impact on Organizational Citizenship Behavior, (iii) Leader Member Exchange is not positive and significant impact on Performance employee, (Iv) Empowerment positive and significant impact on employee performance, (v) Organizational Citizenship Behavior positive and significant impact on employee performance, (vi) Organizational Citizenship Behavior not mediates the influence of Leader Member Exchange on employee performance, (vii) Organizational Citizenship Behavior mediating influence Empowerment on employee performance. Keywords: Leader Member Exchange, Empowerment, Organizational Citizenship Behavior and Performance.